(untitled) (Zeitschrift für Migrationsforschung, 2023)
Durch Migration geprägte Arbeitsfelder bieten Migrant:innen einfachen Zugang zu Beschäftigung, unterscheiden sich aber als Ankunftsarbeit von traditionell berufsfachlich organisierten Arbeitsmarktbereichen. Der Beitrag geht am Beispiel der Gastronomie der Frage nach, wie Zugezogene ihre Ankunftsarbeit deuten. Mit Rückgriff auf das Konzept der sozialen Repräsentation werden folgende migrantisch-subjektive Deutungen vorgestellt: Die Gastronomie wird zwar als ein Ort des Einstiegs in den Arbeitsmarkt gedeutet. Vor dem Hintergrund der jeweiligen Erwerbsbiografie und beruflichen Aspiration aber ergeben sich zwei konfligierende soziale Repräsentationen, in denen die Gastronomie ganz unterschiedlich – nämlich entweder als nichtberuflicher Ort des Umstiegs oder als beruflicher Ort des Aufstiegs – gedeutet wird. Social Representations and Migrants’ Interpretations of Work in the Catering Industry Fields of work characterised by migration provide migrants easy access to employment but differ as arrival labour from labour market sectors traditionally organised by professional requirements. Taking the catering industry as a case, the article explores the question how migrants interpret arrival labour and presents, by resorting to the concept of social representation, interpretations from the subjective perspective of migrants: As a field of entrance the employment in the catering industry is interpreted as a suitable field to access the world of employment. But based on their respective history of employment and professional aspiration migrants further develop two conflicting social representations in which the employment is interpreted entirely different, namely: either as a non-professional field of changeover or as a professional field of advancement.